Hypothyroidism in metabolic syndrome - Kota, Sunil Kumar (Medknow Publications & Media Pvt Ltd, 2012)
AIM: Metabolic syndrome (MetS) and hypothyroidism are well established forerunners of atherogenic cardiovascular disease. Considerable overlap occurs in the pathogenic mechanisms of atherosclerotic cardiovascular disease by metabolic syndrome and hypothyroidism. Insulin resistance has been studied as the basic pathogenic mechanism in metabolic syndrome.[1] This cross sectional study intended to assess thyroid function in patients with metabolic syndrome and to investigate the association between hypothyroidism and metabolic syndrome. MATERIALS AND METHODS: One hundred patients with metabolic syndrome who fulfilled the National Cholesterol Education Program- Adult Treatment Panel (NCEP-ATP) III criteria [ 3 out of 5 criteria positive namely blood pressure ≥ 130/85 mm hg or on antihypertensive medications, fasting plasma glucose > 100 mg/dl or on anti-diabetic medications, fasting triglycerides > 150 mg/dl, high density lipoprotein cholesterol (HDL-C) < 40 mg/dl in males and < 50 mg/dl in females, waist circumference > 102 cms in men and 88 cms in women] were included in the study group.[2] Fifty patients who had no features of metabolic syndrome (0 out of 5 criteria for metabolic syndrome) were included in the control group. Patients with liver disorders, renal disorders, congestive cardiac failure, pregnant women, patients on oral contraceptive pills, statins and other medications that alter thyroid functions and lipid levels and those who are under treatment for any thyroid related disorder were excluded from the study. Acutely ill patients were excluded taking into account sick euthyroid syndrome. Patients were subjected to anthropometry, evaluation of vital parameters, lipid and thyroid profile along with other routine laboratory parameters. Students t-test, Chi square test and linear regression, multiple logistic regression models were used for statistical analysis. P value < 0.05 was considered significant. RESULTS: Of the 100 patients in study group, 55 were females (55%) and 45 were males (45%). Of the 50 persons in control group, 26 (52%) were females and 24 (48%) were males. The baseline characteristics of two groups are depicted in. The two groups were similar with respect to age and sex distribution. However, body mass index, waist circumference, mean systolic pressure, diastolic pressure, fasting blood sugar, total cholesterol, LDL-C, triglycerides and TSH were significantly higher in study group compared to control group. HDL-C was significantly lower in study group.